Optimization Family Food Security Through the Implementation of a Fish and Plant Cultivation System in Buckets in the Yards of the Planjan Village Community - Khasanah, Tuflayfah; Nugraha, Martin Chandra; Raihan, Muhammad Arya Tharif; Ali, Zuanda Aulina; Khasanah, Lis Kartika Nur; Saputri, Yuliana Nur; Awar, Nanda Al Fina; Atiqoh, Septiana Dwi; Zukhrufia, Hanifah; Yusuf, Ibnu; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Planjan Village, Kesugihan District, Cilacap Regency has potential natural resources in agriculture and fisheries; however, the utilization of home yards as a food source remains suboptimal. This community service program aims to enhance household food security through the implementation of the “ Budikdamber ” system (fish and plants cultivation in buckets) combined with simple hydroponic techniques. The program was carried out from July 30 to August 9, 2025, involving two training sessions for farmer groups and residents in several hamlets. The implementation method included a preparation stage (permits, surveys, and provision of tools and materials), delivery of materials (presentations and technical discussions on Budikdamber), and hands-on practice for system assembly and installation. The results showed an increase in participants’ knowledge and skills in using yard space for integrated cultivation of catfish and water spinach. Post-implementation evaluation indicated good plant growth, while some fish mortality occurred due to unstable water quality and oxygen levels. Nevertheless, the program successfully motivated the community to adopt Budikdamber as an alternative to fulfill household needs for animal protein and fresh vegetables independently. In conclusion, the Budikdamber implementation in Planjan Village was effective as a strategy to optimize home yards in supporting sustainable food security.